Benin : Staff Assessment of Qualification for the Multilateral Debt Relief Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Benin reached the completion point under the enhanced HIPC Initiative on March 24, 2003. Staff is of the view that all criteria have been met, and recommends that the Board determine that Benin qualifies for immediate debt relief under the MDRI.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet